2022
DOI: 10.1007/s00784-022-04509-7
|View full text |Cite
|
Sign up to set email alerts
|

Dalbergiones lower the inflammatory response in oral cells in vitro

Abstract: Objectives Periodontitis is a global health burden that underlines the demand for anti-inflammatory treatment. Dalbergia melanoxylon being a rich source of flavonoids has been widely used in traditional medicine but the potential anti-inflammatory activity of its dalbergiones remains to be shown. Material and methods We have isolated 3′-hydroxy-4,4′-dimethoxydalbergione, 4-methoxydalbergione, and 4′-hydroxy-4-methoxydalbergione from Dalbergia melanoxylon a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Although we could not demonstrate anthelmintic activity for the crude extract of D. melanoxylon, mild anthelmintic effects of prenylated isoflavonoids have been reported [48]. Neoflavonoids (represented e.g., by methyl dalbergin (11) and dalbergin (12)) were not included in the biological testing in our study but were previously shown to possess osteogenic properties [37] whereas structurally related dalbergiones from D. melanoxylon exhibited anti-inflammatory effects [49]. Prenylated flavonoids and isoflavonoids play important roles in the defense strategy of plants by protecting them against diseases through a broad inhibition profile against bacteria and fungi [50].…”
Section: Biological Activitymentioning
confidence: 57%
See 1 more Smart Citation
“…Although we could not demonstrate anthelmintic activity for the crude extract of D. melanoxylon, mild anthelmintic effects of prenylated isoflavonoids have been reported [48]. Neoflavonoids (represented e.g., by methyl dalbergin (11) and dalbergin (12)) were not included in the biological testing in our study but were previously shown to possess osteogenic properties [37] whereas structurally related dalbergiones from D. melanoxylon exhibited anti-inflammatory effects [49]. Prenylated flavonoids and isoflavonoids play important roles in the defense strategy of plants by protecting them against diseases through a broad inhibition profile against bacteria and fungi [50].…”
Section: Biological Activitymentioning
confidence: 57%
“…Neoflavonoids (represented e.g. , by methyl dalbergin ( 11 ) and dalbergin ( 12 )) were not included in the biological testing in our study but were previously shown to possess osteogenic properties [ 37 ] whereas structurally related dalbergiones from D. melanoxylon exhibited anti-inflammatory effects [ 49 ].…”
Section: Resultsmentioning
confidence: 99%